Réponses

2014-03-16T16:58:25+01:00
A)7x+5=6+2x soit 7x-2x=6-5 soit 5x=1 soit x=1/5
b)(2x-4)(4x+7)=0 on a donc soit 2x-4=0 soit 2x=4 soit x=4/2 soit x=2
                                     soit 4x+7=0 soit 4x=-7 soit x=-7/4
c)5+(4x+1)=(6x+1)-(5x+3) soit 4x+6 =6x+1-5x-3=x-2 soit 4x+6=x-2 4x-x=-2-6=-8 soit
3x=-8 soit x=-8/3
d)9x²-6x+1=0 on une identité remarquable 9=3² : a²-2ab+b²=(a-b)² ici a=3x et b=1
d'où (3x-1)²=0 soit 3x-1=0 soit 3x=1 soit x=1/3
e)3x+2=-3x+14 soit 3x+3x=14-2=12 soit 6x=12 soit x=12/6 soit x=2
f) (a²)²=16 or 16=4² d'où a²=4 or 4=2² d'où a=2 ou a=-2